Evaluation of Guitars and Violins Made using Alternative Woods through Mobility Measurements - TORRES, Jesus Alejandro; TORRES-MARTINEZ, Reydezel (Archives of Acoustics, 2015)
The feasibility of substituting the types of wood usually employed in the making of guitars and violins was analyzed, but without comparing the properties of involved materials as it is often reported; in this work, the vibrational behavior of twelve guitars and three violins built with alternative types of woods was compared to data of classical instruments available in the literature. In the guitars here measured, the back plate and ribs were not made from traditional woods; while in the violins, only the top plate was made from an alternative type of wood. The results showed that changing the wood of back plate and ribs does not radically affect the typical mobility of a guitar; however, the expected mobility for a violin was not clearly obtained substituting the wood of the top plate. Thus it seems feasible to substitute the wood of back plate and ribs in guitars without causing dramatic changes in their performance; in contrast, a change of the wood type for top plate in violins seems inadvisable unless the design of the top plate is modified to compensate the differences between the woods.